Determinants Of Hajj Saving Intention At Bank Syariah Indonesia - Riska Amalia; Joko Setyono (LPPM ISNJ Bengkalis, 2023)
This study uses religiosity as a moderating variable to analyze the influence of attitudes, subjective norms, perceptions of behavioral control, and financial literacy on the intention to save for the pilgrimage. The research population is the Muslim community on the island of Java. The distribution of questionnaires resulted in 173 respondents by convenience sampling and 157 respondents through purposive sampling. The data analysis technique uses the structural equation model partial least squares (SEM-PLS) with Smart PLS 3.0 software tools. The study results show that attitudes, subjective norms, and financial literacy significantly affect intention, while the perception of behavioral control and religiosity have no effect on intention. Indirectly religiosity cannot strengthen the relationship between the independent variables on the intention to save for the pilgrimage. This research can be used as input in making decisions for Bank Syariah Indonesia (BSI), where factors that have a significant influence can be used as a reference in deciding to increase the intention to save a prospective customer's pilgrimage.